Peran Komunikasi Interpersonal Orang Tua dan Anak dalam Mengatasi Kecemasan Menghadapi Ujian Sekolah - Ayies Devin Seftian; Puri Haraz Alifia; Muhamad Rizaludin; Zikri Fachrul Nurhadi (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
This journal discusses the crucial role of interpersonal communication between parents and children in addressing anxiety before facing school exams at SMP Negeri 1 Garut, utilizing the relational dialectics theory. The method employed in this research is qualitative with a descriptive approach. The objective of this study is to comprehend how interpersonal communication between parents and children can help alleviate anxiety levels before school exams. The data used in this research comprise both primary and secondary data. Primary data were obtained through direct interviews with four children and four parents, including a psychologist. Meanwhile, secondary data encompassed journals, books, and other sources such as online searches or the internet. Data collection techniques used in the study include in-depth interviews, field observations, literature reviews, and online searches. The field research results indicate that interpersonal communication between parents and children plays a highly effective and precise role in reducing the anxiety levels of children before facing school exams.